(untitled) - Abbas, Abul K. (Philadelphia, P.A., 2009)
Expert clinical guidance through the immune system. It provides what it claims; a simple, easy to understand, upto date, immunology text with great, full color pictures and nice tables
Keywords: Immunology,Immunity,Immune System,Miễn dịch học,Sự miễn dịch,Hệ thống miễn dịch; Physiology,Sinh lý học